50-year Deprivation Trajectories: Local Area Change in England and Wales, 1971–2021 - Norman, Paul; Lloyd, Chris; McLennan, David; Ferguson, Sara; Catney, Gemma (Applied spatial analysis and policy, 2024)
Since 1971, the decennial censuses of England and Wales have underpinned the construction of various local level deprivation measures. Many policy-related and academic studies have used deprivation scores calculated cross-sectionally to identify geographical areas in need of regeneration and to explain spatial variations in health outcomes. However, such an approach masks the sometimes very distinct challenges faced in areas with different deprivation histories. There is, therefore, a need to consider the deprivation trajectories of areas over a long time run. This can then enable, for example: monitoring the effects of industry closure; assessing the impacts of area-based planning initiatives; and determining whether a change in the level of deprivation leads to changes in health outcomes. It can also be used to consider what interventions may be linked with positive changes and which could then possibly be implemented elsewhere. Here we extend previous work to cover a 50-year period using input variables relating to employment, housing, and car accessibility, from the six censuses from 1971 to 2021. We identify areas of persistent (dis-)advantage, those areas which have improved their deprivation situation, and those places where the situation has worsened. We cross-classify the changing deprivation measurements with the Office for National Statistics (ONS) Supergroups area classification to thereby determine how different types of area are faring. On average, areas are less deprived in 2021 than in 1971. However, the trajectories of the input variables and of overall deprivation are not linear. The earlier decades are distinctive in rapid falls in non-home ownership and lack of car access but rises and falls in unemployment. The more recent decades have seen rises in non-home ownership and household overcrowding. Geographically, there has been a shift from a widespread level of deprivation, including in more rural areas in 1971, to being more concentrated in urban areas in the 21st Century.